Phosphorous Acid and Phosphoric Acid: When all P Sources are not Equal - Asha M. Brunings; Lawrence E. Datnoff; Eric H. Simonne (EDIS)
While growers are familiar with phosphorus-containing fertilizer, the abundance of terms, apparently similar (such as phosphoric acid and phosphorous acid), may create some confusion on the actual content and efficacy of these products. Some common phosphorus-containing compounds are listed in Table 1. Some claims found in commercial literature and product descriptions refer to phosphorous acid as a “supplemental fertilizer,” while others present it as a fungicide (Table 2). The purpose of this article is to explain what phosphorous acid is and to examine both the fungicidal activity and nutritional value of phosphorous acid. This document is HS1010, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: April 2005.